A pH-responsive iridium(iii) two-photon photosensitizer loaded CaCO3 nanoplatform for combined Ca2+ overload and photodynamic therapy. Issue 16 (4th July 2022) - Shen, Jinchao; Liao, Xinxing; Wu, Weijun; Feng, Tao; Karges, Johannes; Lin, Mingwei; Luo, Hongjie; Chen, Yu; Chao, Hui
Abstract : Synthesis and in-depth biological evaluation of IrCOOH–CaCO3 @PEG for acidic microenvironment responsive and luminescence-guided combined Ca 2+ overload and two-photon photodynamic therapy. Abstract : Intracellular calcium levels are closely related to cell survival. The disruption of the calcium buffering capacity or an overload of the calcium levels enhances the susceptibility of cells towards external stimuli such as reactive oxygen species. Capitalizing on this, herein, a pH-responsive calcium carbonate nanoplatform loaded with Ir(iii ) complexes (IrCOOH–CaCO3 @PEG ) for combined calcium overload and two-photon photodynamic therapy is proposed. Notably, the introduction of the carboxyl group is a core factor to improve the loading content of Ir(iii ) complexes. Upon cellular uptake into cancerous cells, the nanomaterial was found to selectively accumulate in the lysosomes where the acidic environment caused the decomposition of the nanomaterial, releasing the Ir(iii ) complexes and an excess of calcium ions. The combination of calcium overload and the generation of reactive oxygen species upon irradiation by the Ir(iii ) complexes generated a high cytotoxic effect. The loaded nanoplatform demonstrated a strong tumor growth inhibition effect in a breast cancer tumor-bearing mouse model upon exposure to deeply penetrating two-photon irradiation at 750 nm. We strongly believe that the Ir(iii ) complex containing nanoplatform approach we proposed could be a versatile method, and this approach of combining calcium overload therapy and photodynamic therapy holds great potential for cancer therapy.